The Post-2015 European Border Regime. New Approaches in a Shifting Field - Sabine Hess; Bernd Kasparek (Archivio Antropologico Mediterraneo)
Against the background of our recent ethnographic research project on the European border regime in South-East Europe in 2016, the article calls for a re-visiting of established paradigms and approaches in border studies. The article assesses established theoretical conceptualisations of border studies, such as securitisation, externalisation, digitalisation, but also internal mobility regimes and humanitarian rationales. Focussing especially on the vast encampment within Europe, the inner-European buffer zoning, shifting legal foundations as well as new infrastructures of migration control, the authors argue for an extension of theoretical and methodological perspectives of border studies by drawing on insights from legal anthropology and camp and infrastructural studies.